Rhu Keystroke Touchscreen Benchmark - Mohamad El-Abed; Mostafa Dafer; Christophe Rosenberger (2018 International Conference on Cyberworlds (CW), 2018)
BACKGROUND/OBJECTIVE: Down syndrome-associated arthritis (DA) is an underrecognized, inflammatory arthritis that occurs in individuals with Down syndrome. The clinical course, optimal treatment and outcomes are currently unclear. The objective of this study was to identify the clinical presentation and longitudinal outcomes of DA compared with those of juvenile idiopathic arthritis (JIA) using the Pediatric Rheumatology Care and Outcomes Improvement Network (PR-COIN) registry. METHODS: A retrospective case-control study design matched patients with DA to those with JIA on age, gender, arthritis subtype, and medication exposure. Groups were compared at multiple visits (clinical and patient-reported outcomes). Mann-Whitney U test, Fisher's exact test, and generalized linear mixed-effect models were used to compare outcomes between groups. RESULTS: Twenty patients with DA were matched to 100 with JIA. The average intervals between the first and last visits were 3.2 years and 4.6 years for those with JIA and DA, respectively. Most had polyarticular arthritis (70%), while those with DA had more comorbid autoimmune conditions (20% vs. 0%), but no uveitis (0% versus 4%). At the last visit, those with DA had lower arthritis disease activity scores compared with those with JIA [1.8 (2.5) vs. 3.9 (4.2); p=0.02]. The DA group had pain scores that improved over time and trended with disease activity scores. The JIA group had pain scores that increased over time and did not trend with disease activity scores. CONCLUSIONS: With similar disease severity and initial treatment, patients with DA have improved clinical outcomes over time with less active arthritis and reported pain compared with those with JIA.